Psychometric properties of the Food Environment Assessment Survey Tool (FEAST) in people with mobility impairment. Issue 15 (12th October 2021) - Lee, Rebecca E; Suh, Bin C; Cameron, Chelsea; O'Neal, Alicia; Jarrett, Sasha; O'Connor, Daniel P; Ohri-Vachaspati, Punam; Todd, Michael; Hughes, Rosemary B
Abstract: Objective: Approximately one in ten adults under the age of 65 in the USA has a mobility impairing disability. People with mobility impairment generally have poorer dietary habits contributing to obesity and related negative health outcomes. This article presents the psychometric properties of the Food Environment Assessment Survey Tool (FEAST) instrument that measures barriers to accessing healthy food from the perspective of people with mobility impairment (PMI). Design: The current study presents cross-sectional data from two sequential independent surveys. Setting: Surveys were administered online to a national sample of PMI. Participants: Participants represented PMI living throughout the USA. The pilot FEAST survey involved 681 participants and was used to shape the final instrument; 25 % completed a retest survey. After following empirically and theoretically guided item reduction strategies, the final FEAST instrument was administered to a separate sample of 304 PMI. Results: The final twenty-seven-item FEAST instrument includes items measuring Neighbourhood Environment, Home Environment, Personal Control and Access to Support (Having Help, Food Delivery Services, Parking/Transportation). The final four scales had acceptable intra-class correlations, indicating that the scales could be used as reliable measures of the hypothesised constructs in future studies. Conclusions: The FEAST instrument is the first of its kind developed to assess the food environment from the perspective of PMI themselves. Future studies would benefit from using this measure in research and practice to help guide the development of policy aimed at improving access to healthy food and promoting healthy eating in community-dwelling PMI.